Confinement Effect of Geo-grid and Conventional Shear Reinforcement Bars Subjected to Corrosion. (February 2018) - Yalciner, Hakan; Kumbasaroglu, Atila; Ertuc, İbrahim; Turan, Ahmet İhsan
Abstract: An experimental study was performed to examine the effects of polyester geo-grid as a shear reinforcement bar for corroded and uncorroded reinforced concrete beams. The main aim of this study was to investigate the effect of geo-grids on flexural strength, moment-curvature, bond–slip and crack patterns for uncorroded and corroded reinforced concrete beams. For each parameter, a geo-grid confinement technique was compared with conventional reinforced concrete beams as a function of corrosion level. The experimental program consisted of testing ten reinforced concrete beams for two different configurations of shear reinforcement bars at six different corrosion levels (0% and approximately 2, 3, 5, 6, and 9%). Test specimens were subjected to an accelerated corrosion method to corrode the reinforcement bars using a full-scale corrosion pool. Actual corrosion levels were obtained from fully extracted reinforcement bars by breaking the concrete. At the same overall corrosion levels which were differed at longitudinal and transverse reinforcement bars at the same applied corrosion current time for different RC beams. Obtained actual corrosion levels with the aid of fully extracted reinforcement bars from concrete provided to examine the effect of corrosion levels by considering the type of reinforcement bars. The results indicated that the performance of the polyester geo-grid was very poor compared to conventional steel stirrups, even at this stage of corrosion. It was found that the utility of a geo-grid as shear reinforcement bars in reinforced concrete beams is not proper.